The New Sustainability Advantage : Seven Business Case Benefits of a Triple Bottom Line. - Willard, Bob (New Society Publishers, 2012)
Smart sustainability strategies and how they can benefit the bottom line.- Resumé vydavatel
Keywords: environmentální management; environmentální strategie; udržitelný rozvoj; podnikání -- environmentální aspekty; podnikový management -- environmentální aspekty; environmental management; environmental strategy; sustainable development; business -- environmental aspects; industrial management -- environmental aspects; elektronické knihy; příručky; electronic books; handbooks and manuals